Effect of Pharmaceutically Important Cosolvents on the Interaction of Promethazine and Trifluopromazine Hydrochloride with Sodium Dodecyl Sulfate Micelles - GÖKTÜRK, SİNEM (TAYLOR & FRANCIS INC, 2012)
The present study is an attempt to gain a better understanding of the characteristics of binding of phenothiazine drugs; promethazine hydrochloride, and triflupromazine hydrochloride to sodium dodecyl sulfate micellar system in the presence of pharmaceutically important cosolvents, such as ethanol, ethyleneglycol, and propyleneglycol. The interactions of promethazine and triflupromazine hydrochloride with anionic surfactant sodium dodecyl sulfate in the absence and presence of various concentrations of cosolvents have been studied by absorption spectroscopy as a function of surfactant concentration ranging from the premicellar to postmicellar region at 298 K. The binding tendency of promethazine and triflupromazine hydrochloride to sodium dodecyl sulfate micelles decreased with the concentration of cosolvents increased. The addition of cosolvents increased the CMC of sodium dodecyl sulfate and at a certain concentration totally inhibited the micellization. The inhibitory effect of cosolvents on binding of promethazine and triflupromazine hydrochloride to micelles followed the order as; water > ethyleneglycol > propyleneglycol > ethanol. Polarity of the micellar microenvironment and probable location of promethazine and triflupromazine hydrochloride were also discussed in different micellar media.
Keywords: Cosolvent; drug-surfactant interaction; micellar polarity; promethazine hydrochloride; trifluoperazine hydrochloride; X-RAY-SCATTERING; ELECTRONIC ABSORPTION; PHENOTHIAZINE DRUGS; SELF-ASSOCIATION; TRIFLUOPERAZINE; CHLORPROMAZINE; SURFACTANTS; SYSTEMS; TRANSFORMATIONS; SOLUBILIZATION